That-Clauses in Noun Phrase Structure - Acuña Fariña, Juan Carlos (Miscelánea: A Journal of English and American Studies, 1995)
The aim of this paper is to discuss aspects of the grammar of the (non-relative) that-clauses which follow head nouns. Specifically, two aspects will be discussed here. The first has to do with the different types of expansions of head nouns wich can appear under the form of (non-relative) that- clauses. The second concerns the nature of the evidence for positing distinct types of that-clauses in NP structure. In essence, this paper focuses on the complement/modifier divide, as this applies to that-clauses in NP. Central to this discussion will be our attempt to sustain the thesis that that-clause complements to nouns do not exist.